Lightweight SiBCN-modified carbon-bonded carbon fiber composites with directional heat-leading function for efficient thermal protection - Xinqiao Wang; Wentao Wu; Yan Zhang; Baolu Shi; Bin Ma; Xiaoguang Luo; Ning Zhou; Baosheng Xu (Journal of Advanced Ceramics)
Hypersonic vehicles are subjected to critical aerodynamic heating during flight, which poses a substantial challenge for the design of thermal protection systems (TPSs). Carbon-bonded carbon fiber (CBCF) composites are highly valuable materials for TPS in aerospace and military applications because of their lightweight structure and exceptional dimensional stability at elevated temperatures. However, these methods are constrained by a limited capacity for in-plane heat dissipation, which restricts their application under extreme thermal gradients. Therefore, incorporating enhanced in-plane directional heat-leading capabilities into CBCF composite designs represents a highly innovative approach that is expected to alleviate local thermal stress and achieve efficient thermal management. Herein, we propose a multifunctional design strategy involving the fabrication of SiBCN-modified carbon-bonded carbon fiber (CBCF/SiBCN) composites through the integration of high-efficiency in-plane heat conduction pathways with anisotropic thermal insulation structures. The preparation process, microscopic morphology, mechanical response and thermal performance of the CBCF/SiBCN composites were systematically investigated. The fabricated samples exhibited the compressive strength of 4.05–4.36 MPa in the in-plane direction and 1.30–1.36 MPa in the through-the-thickness direction, while maintaining the low density of 0.48–0.49 g·cm-3. Notably, the in-plane thermal conductivity of CBCF/SiBCN reached 60.9–61.5 W·m−1·K−1 while remaining at 0.08 W·m−1·K−1 in the direction of thermal insulation, demonstrating typical anisotropy and indicating significant potential for effective thermal management. This paper introduces an innovative design that focuses on the development of in-plane directional heat-leading properties for thermally insulating composites, which potentially meet the critical requirements for thermal protection in aerospace applications.